Ответ:
x=3
Пошаговое объяснение:
ОДЗ:
0\\&3x-1>0\\&x+5>0\end{cases} \Leftrightarrow \begin{cases}&x>1\\&x>{1\over3}\\&x>-5\end{cases}" alt="\displaystyle\large \begin{cases} &x-1>0\\&3x-1>0\\&x+5>0\end{cases} \Leftrightarrow \begin{cases}&x>1\\&x>{1\over3}\\&x>-5\end{cases}" align="absmiddle" class="latex-formula">
Решаем уравнение:
![\displaystyle\large \log_2{2}+\log_2(x+5)=\log_2(3x-1)+\log_2(x-1)\\\\ \log_2(2x+10)=\log_2((3x-1)\cdot(x-1))\\\\ \log_2(2x+10)=\log_2(3x^2-4x+1)\\\\ 2x+10=3x^2-4x+1\\\\ 3x^2-6x-9=0\\\\ x^2-2x-3=0\\\\ x_1=-1, x_2=3 \displaystyle\large \log_2{2}+\log_2(x+5)=\log_2(3x-1)+\log_2(x-1)\\\\ \log_2(2x+10)=\log_2((3x-1)\cdot(x-1))\\\\ \log_2(2x+10)=\log_2(3x^2-4x+1)\\\\ 2x+10=3x^2-4x+1\\\\ 3x^2-6x-9=0\\\\ x^2-2x-3=0\\\\ x_1=-1, x_2=3](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clarge%20%5Clog_2%7B2%7D%2B%5Clog_2%28x%2B5%29%3D%5Clog_2%283x-1%29%2B%5Clog_2%28x-1%29%5C%5C%5C%5C%20%5Clog_2%282x%2B10%29%3D%5Clog_2%28%283x-1%29%5Ccdot%28x-1%29%29%5C%5C%5C%5C%20%5Clog_2%282x%2B10%29%3D%5Clog_2%283x%5E2-4x%2B1%29%5C%5C%5C%5C%202x%2B10%3D3x%5E2-4x%2B1%5C%5C%5C%5C%203x%5E2-6x-9%3D0%5C%5C%5C%5C%20x%5E2-2x-3%3D0%5C%5C%5C%5C%20x_1%3D-1%2C%20x_2%3D3)
По ОДЗ
1" alt="\displaystyle x>1" align="absmiddle" class="latex-formula">
Значит остается один корень
![\displaystyle x=3 \displaystyle x=3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D3)